Existence of limit cycles in a predator-prey system with a functional response - Basem S. Attili (International Journal of Mathematics and Mathematical Sciences)
We consider the existence of limit cycles for a predator-prey system with a functional response. The system has two or more parameters that represent the intrinsic rate of the predator population. A necessary and sufficient condition for the uniqueness of limit cycles in this system is presented. Such result will usually lead to a bifurcation curve.